Optimising the REE-Zr-Nb potential of eudialyte and its alteration products in the Ilímaussaq complex, South Greenland - Borst, Anouk Margaretha; Mortensen, Henrik Friis; Finch, Adrian Anthony (2017)
Eudialyte-group minerals are complex alkali-zirconosilicates that crystallise in peralkaline igneous rocks known as agpaitic nepheline syenites 1. They provide important unexploited resources for rare earth elements (REE) and other critical metals such as Zr, Nb and Ta1,2,3,4. Europe hosts significant eudialyte deposits in rift-related alkaline intrusions, e.g. Ilímaussaq (Greenland), Lovozero and Khibiny (Russia) and Norra Kärr (Sweden)5. With relatively high contents of the more critical heavy REE, and low U and Th contents compared to conventionally exploited REE phases, eudialyte is particularly attractive as a more sustainable source of REE. Non peer reviewed